Measures of Income. - Mobley, Sybil C. (The Accounting Review, 1968)
Abstract In this article the author illustrates the possibility of preparing different measures of income by application of the previously proposed concept of realization and to examine the uses and the conceptual nature of each measure. A scheme of financial statements expressing different concepts of income measured from different points of realization and serving different, though often related, purposes is presented. The author argues that the interest in dividends is well founded. Dividends are the only truly final stage of income from operations of the enterprise. The ultimate fate of retained earnings is indeterminate but the distribution by the firm of earnings as dividends is final. Conventional income computations for vertically integrated firms measure the net income attributable to the firm's entire sequence of processes. According to the present generally accepted income concept, income is viewed as realized at the point of sale. It is often said that a completely definite report of income for an enterprise is not possible prior to final liquidation and that all interim reports are of a tentative nature.